PREFABRICATED INTERIOR - Schneiderman, Deborah, 1968- ([S.l.] : ROUTLEDGE, 2025)
Though much attention has been given to the prefabrication of architecture, there has been little discussion on the influence and importance of prefabrication within the interior environment. This book does just that, providing a comprehensive investigation into the prefab interior from the19th century to the present and beyond. Each chapter focuses ona typology of the prefabricated interior, looking at the bathroom, kitchen, workspace, furniture, mobile interiors, the prefab house, textiles, wearables, and the digital realm of printed interiors. Taken as a group, these chapters and illustrations indicate that constructs of the interior have been pivotal in the generation of techniques and processes of prefabrication in architecture and the built environment. Chapters explore a diverse range of examples of innovative prefabricated elements and assemblages within interior environments, illustrating the inherent sustainability, accessibility, building efficiency, and affordability of prefabricated design. The culmination of a decade of research by the leading expert on the topic, this will be the go-to resource on prefabricated interiors and an important read for all students and researchers in interior design.
Keywords: Prefabricated interior architecture; ARCHITECTURE / Interior Design / General; ARCHITECTURE / Methods & Materials